2019
DOI: 10.1242/bio.042754
|View full text |Cite
|
Sign up to set email alerts
|

Defining the dynamic chromatin landscape of mouse nephron progenitors

Abstract: Six2 + cap mesenchyme cells, also called nephron progenitor cells (NPC), are precursors of all epithelial cell types of the nephron, the filtering unit of the kidney. Current evidence indicates that perinatal ‘old’ NPC have a greater tendency to exit the progenitor niche and differentiate into nascent nephrons than their embryonic ‘young’ counterpart. Understanding the underpinnings of NPC development may offer insights to rejuvenate old NPC and expand the progenitor pool. Here, we compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…However, ATAC-seq offers many benefits over comparable assays including a lower input material requirement, shorter assay time, in situ library preparation, and further protocol adaptation to fresh-frozen tissue [11]. These advantages have permitted precise in vivo regulatory genomic assays on small populations of sorted cells [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, ATAC-seq offers many benefits over comparable assays including a lower input material requirement, shorter assay time, in situ library preparation, and further protocol adaptation to fresh-frozen tissue [11]. These advantages have permitted precise in vivo regulatory genomic assays on small populations of sorted cells [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin accessibility is a dynamic process that drives nephron development 26 . Nephron progenitors have distinct chromatin accessibility profiles that change as they differentiate 10,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Chromatin accessibility is a dynamic process that drives nephron development 26 . Nephron progenitors have distinct chromatin accessibility profiles that change as they differentiate 10,26 . The role of chromatin accessibility in promotion or inhibition of kidney repair and regeneration has important implications for designing therapies for acute and chronic kidney disease 27 and may help to improve directed differentiation of kidney organoids 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the acetylation of these potential sites would be very likely associated with the nucleus localization of Six2 protein and/or transcriptional activity. Recently, our genome-wide analysis showed that Hdac1 and Six2 co-occupy the enhancer regions of NPC renewal genes and the binding of Hdac1 indicates the open chromatin at the promoter region of actively transcribed genes in NPC [ 34 ]. How HDAC1/2 to regulate Six2 function for kidney development definitely warrants further investigation.…”
Section: The Roles Of Hdacs In the Kidney Developmentmentioning
confidence: 99%